Systems analysis and design - Wu, Shih Yen; Wu, Margaret Schlosser (Minneapolis/St. Paul : West, 1994)
THis book is divided into six parts: An overview of systems analysis and design; The preliminary investigation and analysis phases; Two real-World projects; The modeling tools of systems analysis; The design phase; and The implementation, Installation, and post-implementation review phases.
Keywords: System analysis; System design; System analysis; System design